Identifikasi Struktur Protein Spike Varian Baru SARS-CoV-2 secara Bioinformatika dalam Pengembangan Kandidat Terapi COVID-19 - Taufik Muhammad Fakih; Dwi Syah Fitra Ramadhan; Aulia Fikri Hidayat; Budi Prabowo Soewondo (Jurnal Riset Kimia, 2023)
Despite the relatively slow evolutionary rate of SARS-CoV-2 in comparison to other RNA viruses, the extensive and rapid transmission during the COVID-19 pandemic has led to the emergence of significant genetic diversity since the virus first infected the human population. This has resulted in various variants, such as Alpha (B.1.1.7), Beta (B.1.351), Gamma (P.1), among others. Of particular concern are the Delta Variant and newly recognized Variants of Concern (VOCs), including lineages of B.1.617.2, as well as other VOCs discovered through local transmission, such as Epsilon (B.1.427/29-US) and B1.1.7/E484K-UK. The interactions between these variants and the spike protein of SARS-CoV-2, as well as the Angiotensin-converting enzyme 2 (ACE2), have become a primary focus in understanding the infection and spread of the SARS-CoV-2 virus. This research aims to comprehensively identify, evaluate, and explore the structural characteristics of the macromolecular spike protein of SARS-CoV-2 in the Beta, Gamma, and Delta variants using bioinformatics approaches. The methods employed in this study include homology modeling, molecular docking simulations, and molecular dynamics simulations. The research findings indicate that the spike protein of SARS-CoV-2 in the Gamma variant exhibits a strong affinity for ACE2. Therefore, this study is expected to serve as a reference for designing effective vaccine or antiviral candidates targeting various SARS-CoV-2 variants in the treatment of COVID-19 infections.